PENYULUHAN KESEHATAN DENGAN MEDIA POSTER TERHADAP KETERAMPILAN PENANGANAN PERTAMA LUKA BAKAR DI RUMAH TANGGA DI JETIS DESA GENTAN SUKOHARJO - gatot suparmanto suparmanto (Jurnal Pengabdian Masyarakat Borneo, 2023)
Burns are a form of tissue damage or loss that occurs due to contact with heat sources such as fire, boiling water, hot oil, electric shock and chemicals. One way to overcome the problem so as not to cause casualties is to provide health education about the first treatment of burns. One of the ways to do health education is by using poster media. Poster is one of the health education media that uses pictures accompanied by writing in an attractive and easy to understand form.This service aims to determine whether the effect of health education with poster media on the skills of first handling burns in the household. The method used in this service is Health Education using Poster media. with participants totaling 45 respondents. The pre-test score for the first burn wound treatment skill with adequate category was 0 people (0%), enough category was 0 people (0%), less category was 45 people (100%). Meanwhile, the post-test scores for the first burn wound management skills were in the adequate category as many as 35 people (77.8%), the sufficient category as many as 10 people (22.2%), and the less category as many as 0 people (0%). Based on these values, it can be concluded that there is an effect of health education with poster media on the skill level of first handling burns